2016
DOI: 10.1002/cssc.201600619
|View full text |Cite
|
Sign up to set email alerts
|

Monobenzoporphyrins as Sensitizers for Dye‐Sensitized Solar Cells: Observation of Significant Spacer‐Group Effect

Abstract: A series of monobenzoporphyrins (WH1-WH4) bearing different conjugated spacer groups were designed and synthesized as sensitizers for dye-sensitized solar cells. Although a phenyl spacer only has a minimal impact on the absorption bands of the monobenzoporphyrin, an ethynylphenyl (WH3) or a vinyl (WH4) spacer redshifts and broadens the absorption bands of the dyes to result in much enhanced light-harvesting ability. Dye-sensitized solar cells based on these monobenzoporphyrin dyes displayed remarkable differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 64 publications
(19 reference statements)
2
9
0
Order By: Relevance
“…Herein, we present the synthesis, characterization, and evaluation of a series of β‐functionalized push–pull opp ‐dibenzoporphyrins as sensitizers in DSSCs (Figure ). In a previous publication, we showed that a monobenzoporphyrin bearing vicinal acrylic acid anchoring groups displayed a high power conversion efficiency ( η ) of 5.24 %, which is close to that of the N3 cell obtained under similar conditions ( η =6.92 %). In this work, a push–pull opp ‐dibenzoporphyrin bearing anchoring groups similar to those of monobenzoporphyrin ( WH4 ) displayed a much higher power conversion efficiency ( η =5.9 %) than WH4 ( η =4.81 %) under similar conditions.…”
Section: Introductionsupporting
confidence: 74%
See 3 more Smart Citations
“…Herein, we present the synthesis, characterization, and evaluation of a series of β‐functionalized push–pull opp ‐dibenzoporphyrins as sensitizers in DSSCs (Figure ). In a previous publication, we showed that a monobenzoporphyrin bearing vicinal acrylic acid anchoring groups displayed a high power conversion efficiency ( η ) of 5.24 %, which is close to that of the N3 cell obtained under similar conditions ( η =6.92 %). In this work, a push–pull opp ‐dibenzoporphyrin bearing anchoring groups similar to those of monobenzoporphyrin ( WH4 ) displayed a much higher power conversion efficiency ( η =5.9 %) than WH4 ( η =4.81 %) under similar conditions.…”
Section: Introductionsupporting
confidence: 74%
“…It was reported that slight modification of the donor and/or the acceptor group(s) could make a significant difference in the power conversion efficiency . Our previous work and work from other groups also suggested that different spacer groups between the anchoring group (carboxylic acid group) and the porphyrin core could also bring about significant changes to the power conversion efficiency . It would be interesting to learn what factors determine the power conversion efficiency of these β‐functionalized opp ‐dibenzoporphyrins.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…The synthesis of porphyrin monomer and dimer is illustrated in Scheme . The starting compound, 2,3‐dibromoporphyrin 1 was synthesized using published two‐step procedure ,. Then one benzene ring was fused at the porphyrin β, β′‐position by Pd 0 ‐catalyzed Heck reaction followed by one‐pot cyclization and aromatization to give monobenzoporphyrin 2 ,.…”
Section: Resultsmentioning
confidence: 99%